Comets : visitors from deep space - Eicher, David J., 1961- (New York, NY : Cambridge University Press, 2013)
Join David J. Eicher in this fast-paced and entertaining journey through the history, present, and future of these important yet mysterious cosmic bodies. From ancient times, humans have been fascinated by "broom stars" and "blazing scimitars" lighting up the sky and moving against the fixed background of stars. The Great Comets of our time still receive in-depth attention - ISON, Hale-Bopp, Hyakutake, West, and others - while recent spacecraft encounters offer amazing insight into the earliest days of the solar system. In this guide you will discover the cutting-edge science of what comets are, how they behave, where they reside, how groups of comets are related, and much more. The author carefully explores the ideas relating comets and life on Earth - and the danger posed by impacts. He finishes with practical, how-to techniques, tips, and tricks of how to successfully observe comets and even to capture your own images of them."--From publisher description.
Strange lights in the sky -- Great comets of the past -- What are comets? -- Comets of the modern era -- Comets in human culture -- Where comets live -- The expanding science of comets -- Observing comets -- Imaging comets.
Includes bibliographical references and index.
Keywords: Comets; Comets